EFL STUDENTS’ PERCEPTION ON THE TEXTBOOK SELECTED BY THEIR COURSE INSTRUCTOR - Radiatan Mardiah (Universitas Jambi, 2022)
Students perception on selected textbook they use can be a meaningful information in helping them achieve their learning goal and generally in helping the teacher in designing the course. This paper was aimed at describing EFL students’ perception on a selected textbook entitled Second Language Acquisition: An Introduction written by Muriel Saville-Troike published in 2012. The participants of this descriptive study were 40 EFL students enrolled in Second Language Acquisition course in academic year 2019/2020 in a public university in Jambi, Indonesia. The data were gathered through questionnaire response and WhatsApp discussion. It was revealed that majority of the students perceive that the book is informative, useful, and needed but difficult to understand. The students suggested to develop additional simple material to the book which consist of brief explanation and example, easy to understand words, and have interesting and eye-catching design. This information could be used to design and develop additional course material.